Estudo de caso em aulas de ciências: contribuições para o desenvolvimento do pensamento crítico na educação básica - Gama, Thamires Valadão (Universidade Federal de São Carlos, 2019)
In contemporary society, products of science significantly affect people´s decisions, making critical thinking a valuable skill to be developed. Among the methodologies which can encourage critical thinking, there is one that is based on using case studies in teaching environments. Moreover, they are understood as narratives that carry an educational message. The aim of this work is to investigate the contribution of an experiment carried out in regular Science classes to develop students´ critical thinking in which a case study was used as the basis for following a jigsaw procedure, as a cooperative learning strategy. Therefore, critical thinking indicators were determined during the initial and final stages of the didactic activity, which was conducted during the case study called "The Clumsy Baker" by five groups of students. The data analysis shows that an improvement in the critical thinking indicators occurred in all the groups, particularly for indicators: "Association of Ideas" and "Critical Assessment". Furthermore, the students´ perceptions concerning the activity showed they accepted it well. In view of the above, it was concluded that using case studies, as well as cooperative activities, mainly those based on the jigsaw format, favors the development of critical thinking, and is therefore appropriate for the context of teaching science at Middle School. Key-words: Case studies; Jigsaw; Critical Thinking; Science; Middle School.
A case study in science classes: contributions to develop critical thinking in basic education
Keywords: Estudos de caso; Jigsaw; Pensamento crítico; Ciências; Ensino fundamental II; Case studies; Critical thinking; Science; Middle School; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO